Fertility properties and humic fractions in a Rhodic Ferralsol in Brazilian Cerrado - Fontana, Ademir; Pereira, Marcos Gervasio; Loss, Arcângelo; Cunha, Tony Jarbas Ferreira; Salton, Júlio César (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this study was to evaluate fertility attributes and the fractions of organic matter, fulvic acid, humic acid, and humina, in a Rhodic Ferralsol, under different cultivation systems in Brazilian Cerrado. The experiments were carried out from 1993 to 2003. The treatments were divided in four groups: tillage (1 and 7), rotation tillage/pasture (3 and 5), rotation pasture/tillage (4 and 6), and continuous pasture (2 and 8), all in no-tillage system. Chemical analyses of soil samples were made for the depth of 0–20 cm, after ten years of cultivation. It was observed that Ca2+ content varied from 4.6 cmolc kg-1 (tillage) to 6.20 cmolc kg-1 (continuous pasture), and available P from 1 to 6 mg kg-1. The Mg2+ content varied from 3 cmolc kg-1, under tillage/pasture, to 3.8 cmolc kg-1 in continuous pasture, and K+, from 0.28 cmolc kg-1, under continue pasture, to 1.10 cmolc kg-1 in tillage/pasture. It was verified that organic C content varied from 16.6 g kg-1 in the tillage, to 28.8 g kg-1under tillage/pasture. The humine fraction presents the largest values among the organic matter fractions.